Isolation of two antifungal compounds fromNeolitsea cuipala and their activity against some plant pathogenic fungi - Boruah, P; Bhuyan, P D; Dutta, S C; Mohan, S; Mathur, R K (Folia microbiologica, 1999)
Zeylanidine and zeylanicine isolated fromNeolitsea cuipala fruit peels are found to be potential antifungal agents againstHelminthosporium oryzae, Fusarium oxysporum, Alternaria solani, Curvularia varuciformis andColletotrichum gleosporioides.